Cultural Dynamics: Pangadâ' in the Bhâkalan and Nyeddèk Kabhin Process in Madura 'Urf Perspective: Dinamika Kultural: Pangadâ' dalam Proses Bhâkalan dan Nyeddèk Kabhin di Madura Perpektif 'Urf - Ludfi Ludfi (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2022)
This research explores weddings in Madura, especially the unique role of Pangadâ' in the bhâkalan (engaged) and nyeddèk kabhin (spokesperson) processes. This research explores Islamic law and social institutions in Madura with an integrated phenomenological approach to everyday life. Data was collected through observation, interviews and document analysis using Spradley's four activity flow model, providing an in-depth understanding of the culture and values of Madurese society regarding marriage. This research succeeded in revealing the role of Pangadâ' not only involved in conventional stages, but also in special steps such as nyareh ngen-angen, masang ngen-angen, nyalabhâr, nyareh dhinah bhâgus, mentah and dispute resolution. His involvement was influenced by local traditions and wisdom, creating a Madurese wedding identity. In the 'urf perspective, these traditions are categorized as 'urf 'amalī and 'urf ṣaḥīḥ, indicating harmony with Islamic values. This research visualizes the harmony between local traditions and Islamic values in the context of Madurese weddings, depicting harmonious integration.